지하수 내 질산성 질소 반응-이동 모델링을 위한 부지특이적 탈질화계수 선정 방안에 대한 고찰 - 김상현; 정재식; 이승학 (한국지하수토양환경학회, 2021)
A simple and efficient scheme is presented that attempts to implement the site-specific denitrification rate in the reactivetransport modeling for the nitrate in groundwater. A series of correlation analyses were conducted using 133 datasetsobtained from different nitrate-contaminated sites to find the empirical relationships between denitrification rates andvarious subsurface properties. Based on Pearson’s correlation analysis, the soil organic carbon concentrations showed astatistically significant correlation (r = 0.75, p < 0.05) with the denitrification rates. A linear regression was performed,which could be utilized to effectively determine the site-specific denitrification rate based on the soil organic carbonconcentration of a site. The proposed method is expected to effectively replace the conventional methods which eitherwere too complicated for practical application or impose large uncertainties that might end up with unreliable results.